Results and scientific significance of the Sibiryakov’s (Yakut region) expedition (1894 -1896) (Revista de Investigaciones Universidad del Quindío, 2023)
This article considers the scientific results of the first comprehensive stationary expedition studying the indigenous peoples of Eastern Siberia – the Sibiryakov’s (Yakut region) expedition of the East Siberian Department of the Russian Geographical Society (1894-1896). This study aims to identify the scientific significance of publications based on the results of the expedition in the source study aspect, which will allow us to consider the history of the accumulation of knowledge about the Yakut language (Sakha language) and Yakut literature (Sakha literature) of the 19th-20th centuries, and will replenish the source study base of historical and literary science. During the research, systematic and holistic approaches, as well as contextual, interpretive, historical-literary and comparative methods of scientific research were used in the study of the source. In this regard, the study of the dictionary of the Yakut language by E.K. Pekarsky gains increasing relevance in the problematics of supertext, both its linguistic value and its significance in the historical and cultural terms are highlighted. As a result of the study, special importance is given to the role of a persons exiled for political reasons to Yakut region, who became participants in this expedition, which undoubtedly had a favorable effect on the results of field research and the fate of the exiled themselves. Precisely the involvement of these young people in the work of the expedition enabled to collect and publish scientific works on the beliefs of the Yakuts (Sakha people), folklore and the Yakut language, which laid the foundation for the development of the Yakut people’s verbal folklore. It is no less valuable that owing to the work of the exiles, it was possible to attract representatives of the local population to further scientific study of their language, culture and region, the spiritual and moral influence of the Russian language and culture on the development of the national region as a whole.
Keywords: source; scientific results; source study base; indigenous peoples of Eastern Siberia; Sibiryakov’s (Yakut region) expedition; “Dictionary of the Yakut language” by E.K. Pekarsky; political exiles of Yakut region